Pemodelan Bahaya Erosi Tanah Berbasis USLE dan SIG di DAS Olaya, Sulawesi Tengah - Andayani, Susi (Universitas Tadulako, 2025)
Soil erosion is a critical environmental issue that directly contributes to land degradation and reduced productivity in watershed areas. This study aims to analyze the dynamics of soil erosion hazard in the Olaya Watershed, Central Sulawesi, using the Universal Soil Loss Equation (USLE) model integrated with Geographic Information Systems (GIS). The analysis was conducted for two temporal periods, 2020 and 2023, to assess changes in erosion rates and the spatial distribution of erosion hazard. The model incorporates key parameters including rainfall erosivity (R), soil erodibility (K), slope length and steepness (LS), and land cover-management factor (CP). All spatial data were processed in raster format and analyzed using ArcGIS 10.7 software. The results indicate that the average annual soil erosion rate decreased from 333.70 tons/ha/year in 2020 to 173.57 tons/ha/year in 2023. This decline was influenced by changes in rainfall erosivity. Based on the Erosion Hazard Index (EHI) classification, most of the watershed area was categorized as having severe erosion hazard in 2020, which shifted to moderate in 2023. These findings highlight the importance of spatio temporal monitoring in watershed management and the urgent need for land conservation efforts based on prioritized zonation to mitigate erosion risks in tropical regions. Keywords: soil erosion, land conservation, USLE model, geographic information system, erosion dynamics, Olaya Watershed